Serum parathyroid hormone and total serum calcium levels in mild & severe preeclampsia versus normal pregnancy - Shalal, Maad M.; Miran, Najmah M.; Mohammad, Inaam F. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Preeclampsia (PE) is a major cause of maternal morbidity and mortality, complicating 3-14% of all pregnancies. Although the etiology remains unknown, placental hypoperfusion and diffuse endothelial cell injury are considered to be the central pathological process; many endocrinological changes have been linked to the etiology of preeclampsia including parathyroid hormone and calcium level.Objective: to compare serum parathyroid hormone and total serum calcium levels in mild and severe preeclampsia versus normal pregnancy.Patients and methods: Serum parathyroid hormone (PTH) level and total serum calcium level were measured in thirty normotensive pregnant women and thirty women with mild preeclampsia and thirty women with severe preeclampsia using Enzyme Linked Immuno- Sorbent Assay (ELISA) test for parathyroid hormone & colorimetric test for total serum calcium. All pregnant women enrolled in the study had similar demographic background. Patient and control groups were matched for age, and gestational age.Results: Total serum calcium level was decreased and parathyroid hormone level was elevated in preeclamptic women compared to normotensive women with significantly lower total serum calcium (7.43 ± 0.68) and higher level of parathyroid hormone (93.84 ±10.63) in severe preeclampsia compared to mild preeclampsia group where total serum calcium was(8.02±1.02) and parathyroid hormone was (79.34 ±6.04).With p value